Islamic Corporate Governance (Case Study in Asia and GCC Countries) - Ummu Salma Al-Azizah (Universitas Muhammadiyah Prof. DR HAMKA., 2017)
In the recent years, Islamic Banking development has many contribution into the International finance. However, this followed by other industries such as capital market and also corporate. Therefore, need to understanding how is Islamic Corporate Governance should be follow by the industries. In this paper, elaborate some Islamic Corporate Governance in ASIA and GCC Countries as well as established during the year, there are: Indonesia, Malaysia and Pakistan. And from GCC are: Saudi Arabia, Dubai and Bahrain.